VERBAL AND NONVERBAL ASPECTS OF TED TALKS VIDEOS TO DEVELOP LEARNERS’ PUBLIC SPEECH - Feruzakhon Mansurova (International Scientific and Current Research Conferences, 2023)
This thesis statement discusses the role of TED Talks in developing learners’ public speaking ability which is considered to be one of the most challenging skills. It proves that TED Talks offer up-to-date information and motivational experience to help students to deliver a proper public speech. Besides, it reveals that TED Talks videos include both verbal and nonverbal aspects for students’ linguistic development.